Effect of static magnetic field on pain level and expression of P2X3 receptors in the trigeminal ganglion in mice following experimental tooth movement. Issue 1 (21st October 2016) - Zhu, Yafen; Wang, Shengguo; Long, Hu; Zhu, Jingyi; Jian, Fan; Ye, Niansong; Lai, Wenli
Abstract : Recent research has demonstrated that static magnetic fields (SMF) can generate an analgesic effect in different conditions. The present study explored effects of SMF on pain levels and expressions of P2X3 receptors in trigeminal ganglion (TG) in mice after experimental tooth movement (tooth movement induced by springs between teeth). Experiments were performed in male mice (body mass: 25–30 g) and divided into SMF + force group, force group, and no force group. Exposure time was over 22 h per day. Mouse Grimace Scale was used for evaluating orofacial pain levels during experimental tooth movement at 4 h and 1, 3, 7, and 14 days. Meanwhile, expression levels of P2X3 receptors in the TG were evaluated by immunohistochemistry and western blotting at same time points. We finally found that during experimental tooth movement, pain levels of mice peaked at 3 days, and then decreased. While pain levels of mice were reduced in the SMF environment at 4 h, 1 and 3 days, there was a significant difference at 1 and 3 days. Meanwhile, under the action of SMF, expression levels of P2X3 receptors in TG were significantly lower at 4 h, 3 and 7 days. These results suggest that SMF can reduce pain levels in mice, and down‐regulate P2X3 receptors in TG. Bioelectromagnetics. 38:22–30, 2017. © 2016 Wiley Periodicals, Inc.